Systematic Review of Plastic Waste as Eco-Friendly Aggregate for Sustainable Construction - Adiyanto, Okka; Mohamad, Effendi; Abd Razak, Jeefferie (International Journal of Sustainable Construction Engineering and Technology, 2022)
The advent of the COVID-19 pandemic has increased the amount of plastic waste. The demand for food and plastic-packaged foodstuffs has increased, and the use of disposable utensils has increased. The large usage of plastic packaging was the main factor which contributed to the plastic waste disposal. Since these plastic wastes are not easily degraded, it has led into massive environmental pollution. Transitioning towards eco-friendly materials for new sustainable technologies will be critical to combating future pandemics and reduce the plastic waste. Hence, recycling of plastic waste and its re-utilization as green and eco-friendly construction material could decrease the tendency of environmental pollution. In this review paper, we have presented an overview of the published articles which recycled plastic waste as an eco-friendly aggregate material for different construction-based applications before COVID 19 and during COVID 19. Furthermore, the processing methods which were suggested in the published articles for recycling plastic waste have been discussed. A few construction materials could be developed by utilizing the plastic wastes, including the polymer-modified asphalt mixes, eco-bricks, and construction and demolition materials. These products could be used as novel products for other sustainable applications and benefits of circular economy. According to several reports, polymeric based plastic wastes can be effectively used as a recycled material, decrease the demand for traditional materials and also tremendously reduce the construction costs.